Dietary patterns of students in the Claro M. Recto High School and the implications for health education - Garcia, Fe Casillan 1936- (1971)
This study was conducted to determine the dietary patterns of students in the Claro M. Recto High School during the school year 1975-1976. The descriptive method of research was used in the study. The reasons for the choice of food items were ranked in decreasing order: inherent characteristics like taste, color, odor and texture; they were served at home; and they had a favorable effect on health.
Appendices: leaves 185-221
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Diet -- Philippines -- Manila; Health education (Secondary) -- Philippines -- Manila; Youth -- Nutrition. -- Philippines -- Manila